THE ROLE OF 3D TECHNOLOGIES IN PLANNING CONSTRUCTION INSTRUCTIONS (Conferencea, 2024)
3D technologies have revolutionized various industries, particularly construction, where precise planning, visualization, and execution are critical. This article explores the integration of 3D technologies in the planning of construction instructions, emphasizing their advantages in improving accuracy, efficiency, and communication within construction projects. We will examine how 3D modeling, simulations, and virtual reality (VR) can facilitate better understanding among stakeholders, reduce costs, and enhance safety protocols in the construction process.